2014
DOI: 10.1080/14786419.2014.939084
|View full text |Cite
|
Sign up to set email alerts
|

Identification of chemical compounds present in different fractions of Annona reticulata L. leaf by using GC–MS

Abstract: GC-MS analysis of fractions prepared from hydro-alcoholic extract of Annona reticulata Linn (Family Annonaceae) leaf revealed the presence of 9,10-dimethyltricyclo[4.2.1.1(2,5)]decane-9,10-diol; 4-(1,5-dihydroxy-2,6,6-trimethylcyclohex-2-enyl)but-3-en-2-one; 3,7-dimethyl-6-nonen-1-ol acetate; 9-octadecenamide,(Z)-; glycerine; D-glucose,6-O-α-D-galactopyranosyl-; desulphosinigrin and α-methyl-D-mannopyranoside as few of the major compounds in different fractions. The presence of these compounds in the plant has… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 3 publications
0
6
0
Order By: Relevance
“…The results observed may be attributed to the compounds present in ethyl acetate fraction. The major compounds 9-octadecenamide, (Z)-, ethyl isoallocholate and 9,10-secocholesta-5,7,10(19)-triene-3,24,25-triol, (3α,5Z,7E)-present in ethyl acetate fraction [8] may be considered as compounds responsible for the observed anti-hyperglycemic activity. The compound 9, 10-secocholesta-5, 7, 10(19)-triene-3,24,25-triol, (3α,5Z,7E)-is a hydroxyl derivative of vitamin D3 and vitamin D3 is known to have a positive effect in the management of diabetes [14][15][16].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The results observed may be attributed to the compounds present in ethyl acetate fraction. The major compounds 9-octadecenamide, (Z)-, ethyl isoallocholate and 9,10-secocholesta-5,7,10(19)-triene-3,24,25-triol, (3α,5Z,7E)-present in ethyl acetate fraction [8] may be considered as compounds responsible for the observed anti-hyperglycemic activity. The compound 9, 10-secocholesta-5, 7, 10(19)-triene-3,24,25-triol, (3α,5Z,7E)-is a hydroxyl derivative of vitamin D3 and vitamin D3 is known to have a positive effect in the management of diabetes [14][15][16].…”
Section: Discussionmentioning
confidence: 99%
“…Glycerine is capable of causing hyperglycemia in animals after oral or intraperitoneal administration [21]. The phytochemical analysis also revealed that methanolic fraction and residual fraction contains several other compounds such as sugar like [8] in nature. Hence, the presence of glycerine and other sugar like compounds as major components may be the reason due to which the methanolic fraction and residual fraction had not been able to show any kind of anti-hyperglycemic effect at the tested dose level.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The extract was filtered and concentrated by rotary evaporator. For the preparation of different fractions method was used [7][8][9].…”
Section: Plant Materialsmentioning
confidence: 99%